Barisan Tani Indonesia (BTI) pada Masa Revolusi Indonesia, 1945-1950 - Willy Alfarius (Lembaran Sejarah, 2023)
This article discusses the process of forming Barisan Tani Indonesia (BTI) in 1945, the work programs they offered to improve the welfare of the peasants, and the dynamics that occurred within the organization throughout the Indonesian Revolution (1945-1949). In particular, this article highlights the emergence of ideas and discourses that are used as a basis for determining their work programs. This article uses historical methods to explore various sources such as newspapers and magazines published in the period in context and previous studies on the BTI. This article argues that agricultural modernization was one of the most dominant work agendas raised and offered by BTI. Discourse regarding agricultural modernization appears in various publications they produce. They consider agricultural modernization to be an important key to improving the welfare of Indonesian peasants, as has happened in Europe and America. However, throughout the first five years of BTI's existence, especially during the Indonesian Revolution, many work programs were not implemented due to the war situation. Following the end of the War of Independence in 1949, the BTI could reorganize its organization and carry out its work program, marked by the Third BTI Congress in 1950.